Reversine inhibits proliferation and induces apoptosis of human osteosarcoma cells through targeting MEK1 - Xianlong Chen; Yeyin Zhong; Simiao Wang; Shujie Xu; Junyuan Chen; Xin Cheng; Xuesong Yang (Journal of Bone Oncology, 2024)
Reversine, or 2-(4-morpholinoanilino)-6-cyclohexylaminopurine, is a 2,6-disubstituted purine derivative. This small molecule shows anti-tumor potential by playing a central role in the inhibition of several kinases related to cell cycle regulation and cytokinesis. In this study, systematic review demonstrated the feasibility and pharmacological mechanism of anti-tumor effect of reversine. Firstly, we grafted MNNG/HOS, U-2 OS, MG-63 osteosarcoma cell aggregates onto chicken embryonic chorioallantoic membrane (CAM) to examine the tumor volume of these grafts after reversine treatment. Following culture, reversine inhibited the growth of osteosarcoma cell aggregates on CAM significantly. In vitro experiment, reversine suppressed osteosarcoma cell viability, colony formation, proliferation, and induced apoptosis and cell cycle arrest at G0-G1 phase. Scratch wound assay demonstrated that reversine restrained cell migration. Reversine increased the protein expression of E-cadherin. The mRNA expression of Rac1, RhoA, CDC42, PTK2, PXN, N-cadherin, Vimentin in MNNG/HOS, U-2 OS and MG-63 cells were suppressed and PTEN increased after reversine treatment. Network pharmacology prediction, molecular docking and systematic review revealed MEK1 can be used as an effective target for reversine to inhibit osteosarcoma. Western blot results show the regulation of MEK1 and ERK1/2 by reversine was not consistent in different osteosarcoma cell lines, but we found that reversine significantly inhibited the protein expression of MEK1 in MNNG/HOS, U-2 OS and MG-63. All these suggested that reversine can exert its anti-tumor effect by targeting the expression of MEK1.